Silicon-based film on the yttria-stabilized tetragonal zirconia polycrystal: Surface and shear bond strength analysis - Silva, Alecsandro de Moura [UNESP]; Figueiredo, Viviane Maria Gonçalves de [UNESP]; Massi, Marcos; Prado, Renata Falchete do [UNESP]; Silva Sobrinho, Argemiro Soares da; Queiroz, José Reinaldo Cavalcanti de; Nogueira Junior, Lafayette [UNESP] (Wiley, 2019)
AIM: To analyze the effect of a silicon (Si)-based film deposited on yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) on the topography and bond strength of resin cement. METHODS: Specimens of zirconia were obtained and randomly divided into 4 groups, according to surface treatment: polished group (PG) zirconia; sandblasted group (SG) zirconia with aluminum oxide (100 µm); after polished, zirconia was coated with Si-based film group (SiFG); and after sandblasted, zirconia was coated with Si-based film group (SiFSG). The Si-based films were obtained through plasma-enhanced chemical vapor deposition. Surface roughness and contact angle analysis were performed. Resin cement cylinders were built up on the treated surface of blocks, after applying Monobond-S. The specimens were submitted to thermocycling aging and shear bond strength testing. The Kruskal-Wallis and Mann-Whitney U-tests were performed. RESULTS: There were significant differences between the surface treatments for each roughness parameter measured. Si-based film increased roughness and decreased the contact angle. Si-based film groups also demonstrated significantly lower bond strength values. CONCLUSION: Si-based film produced using plasma deposition provided lower bond strength to resin cement compared with conventional treatment; however, the film deposition reduced the contact angle and improved roughness, favorable properties in the long way to prepare an optimum material.
Keywords: adhesion; plasma-enhanced chemical vapor deposition; roughness; shear bond strength; zirconia